Machine learning techniques for adaptive multimedia retrieval : technologies, applications, and perspectives - Wei, Chia-Hung, 1973-; Li, Yue, 1980- (Hershey, PA : Information Science Reference, 2011)
"This book disseminates current information on multimedia retrieval, advancing the field of multimedia databases, and educating the multimedia database community on machine learning techniques for adaptive multimedia retrieval research, design and applications"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Interactive multimedia -- Databases; Information retrieval; Automatic indexing; Database management; Machine learning